2005
DOI: 10.1111/j.1540-8159.2005.50033.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Magnetic Resonance Imaging Safe in Cardiac Pacemaker Recipients?

Abstract: Magnetic resonance imaging (MRI) is currently contraindicated in cardiac pacemaker (PM) recipients. The objectives of this prospective study were to (1) reassess the risks of performing an MRI scan in patients with PM, (2) compared the pacing functions before and after the exposure to MRI, and (3) monitor the development of possible adverse effects. Thirteen patients implanted with an Affinity DR model 5330 PMs (St. Jude Medical) connected to a Tendril model 1388 leads (St. Jude Medical) underwent 2.0 T-MRI fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The function of the pacemaker device and leads remained stable in all patients immediately after MRI and at follow-up (101 days) with no significant changes in lead impedances, capture thresholds, sensing signal amplitudes, or battery voltage being detected compared with interrogation performed immediately before MRI. This is in accordance with the findings of other groups, suggesting that MRI of different anatomic regions may be performed safely in selected patients with pacemaker/implantable cardioverter defibrillator systems under well-controlled circumstances at 0.5, 9 11 1.5, 2 , 8 , 12 21 2, 22 and 3 T 23 24 …”
Section: Discussionsupporting
confidence: 91%
“…The function of the pacemaker device and leads remained stable in all patients immediately after MRI and at follow-up (101 days) with no significant changes in lead impedances, capture thresholds, sensing signal amplitudes, or battery voltage being detected compared with interrogation performed immediately before MRI. This is in accordance with the findings of other groups, suggesting that MRI of different anatomic regions may be performed safely in selected patients with pacemaker/implantable cardioverter defibrillator systems under well-controlled circumstances at 0.5, 9 11 1.5, 2 , 8 , 12 21 2, 22 and 3 T 23 24 …”
Section: Discussionsupporting
confidence: 91%
“…The safe performance of MRI at 1.5 T in ICD recipients was first reported by Gimbel and colleagues (8). Several relatively small studies have also reported overall safety (7, 10, 30, 33, 34). Several investigators have reported a lack of change in troponin-I levels as a surrogate of myocardial damage after MRI (11, 12, 35), and recent reports have demonstrated the overall safety of repeated MRI (36) and MRI without SAR restrictions in device recipients (26).…”
Section: Discussionmentioning
confidence: 99%
“…These forces are directly related to the amount and shape of the ferromagnetic content, the location of this content in relation to the MR system, and the strength of the static magnetic field [88]. Although excessive magnetic field interactions can theoretically cause device movement, prospective data on both "standard" and MR conditional pacemakers at 1.5 Tesla did not demonstrate significant clinical effects [32,57,81]. …”
Section: Introductionmentioning
confidence: 99%